Internationalization at the College of Business, JBLFMU-Molo Through Collaborations: Benefits, Challenges, and Prospects - Alimen, Rolando; Pador, Glenito (JPAIR Institutional Research, 2017)
Internationalization is a challenge that the maritime university (JBLFMU-Molo) faces against a domestic as well as global backdrop. In response to this challenge, this study discussed the merits of educational reform anchored on a distinct orientation of internationalization. Thus, the College of Business of JBLFMU-Molo started the different multinational activities that focus on the need of the maritime university to integrate international dimension into maritime business-related education. The researchers employed qualitative method through interview utilizing an open-ended instrument as a mode of data collection. Findings reveal that the flexibility of students and exposure to the international curriculum were the major important elements achieved through internationalization. Students who were exposed to international collaboration adjust to international culture and communication. Opportunities and prospects of internationalization lead to more exposure to international trends, issues in maritime and business education, linkages in the business and education aspects, quality assurance, accreditation, and distance education. Through internationalization, educational reforms will be enhanced at the college. The study recommends that the administration of JBLFMU-Molo will be used as basis to continuously build closer linkages and increase more collaboration in student mobility, memoranda of agreement, and other programs to improve the overall quality of maritime and business-related education in the ASEAN region.